PENGGUNAAN MODEL MIND MAPPING UNTUK MENINGKATKAN HASIL BELAJAR PKN PADA SISWA KELAS IV SDN 012 MALINAU UTARA TAHUN PELAJARAN2016/2017 - Eka Selvi Handayani (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2017)
The purpose of this research is to improve the learning outcomes of Civic Education in using mind mapping in grade IV SDN 012 North Malinau Academic Year 2016/2017. In this study, researchers concluded that the problem in this study is whether the use of mind mapping method can improve student learning outcomes in subjects Civic Education in fourth grade SDN 012 North Malinau. This research is a classroom action research (CAR) conducted in SDN 012 North Malinau precisely the class IV SDN 012 totaling 30 people. Data collection techniques used in this study is the observation, documentation and a written test. The experiment was conducted with two cycles and each cycle consisting of 2 meetings. Based on observational data obtained at each cycle can be seen more and more day by using mind mapping can improve student learning outcomes. Based on the recapitulation of observations improving student learning outcomes by using mind mapping in cycle 1 reached 50% with an average value of 67.26 and the second cycle increased 96.66% with an average value of 77.76 according to the indicators of success. The conclusion of this study is through the use of mind mapping methods to improve learning outcomes of Civic Education in grade IV SDN 012 North Malinau Academic Year 2016/2017